China and the World in a Changing Context Perspectives from Ambassadors to China - Wang, Huiyao; Miao, Lu (China and Globalization,, 2022)
This book is open access under a CC BY-NC-ND license. Ambassadors are a kind of vehicle and bellwether for globalization. These diplomatic envoys serve as pivotal contact points between nations across a wide range of fields, from economics and culture to health and the environment. The special group of ambassadors in this book - those based in Beijing - are at the forefront of what for many countries is one of their most important bilateral relationships, as well one of the most striking and consequential aspects of global affairs in the 21st century: the rise of China on the world stage. This book aims to present an overview of China and the world from diverse angles. It brings together essays by ambassadors to China on a range of bilateral and multilateral issues, including trade and investment, regional economic cooperation, sustainable development, technology and innovation, and entrepreneurship. Given their familiarity with China and extensive international experience, the insights of these ambassadors are useful for policymakers, academics, entrepreneurs, students, and anyone trying to make sense of our rapidly changing world.